Animal health and the role of communities: an example of trypanasomosis control options in Uganda - McCarthy, Nancy; McDermott, John; Coleman, Paul (International Food Policy Research Institute, 2003)
In many African countries, governments are re-thinking the role of the state in centrally providing certain goods and services. The rights and responsibilities for providing various public goods are being decentralized to lower levels of government administration, and/or being devolved directly to local citizens or user groups themselves. It is thus critical to ask: under what circumstances will local groups provide the socially optimal level of the public good? In this paper, we apply this question to the case of controlling an important vector-borne livestock disease in Uganda, trypanosomosis, which is transmitted by the tsetse fly. We investigate the underlying epidemiology of transmission and different options for control, and the implications for group provision of control, within the framework of a game-theoretic model. Results indicate that individual incentives to uptake tsetse and trypanosomosis control differ widely across different control methods. Since the costs of successfully implementing collective action are affected by individual incentives to participate in collective action, the model predicts which method/s are likely to be successfully implemented at the community level. More broadly, the model highlights under what circumstances community-provision is not likely to be optimal, depending on the underlying epidemiology of the disease, technological parameters, prevailing market characteristics, and socio-cultural conditions.